2016
DOI: 10.1002/jbmr.3070
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Inflammatory Index, Bone Mineral Density, and Risk of Fracture in Postmenopausal Women: Results From the Women's Health Initiative

Abstract: Previous studies suggest that bone loss and fracture risk are associated with higher inflammatory milieu, potentially modifiable by diet. The primary objective of this analysis was to evaluate the association of the dietary inflammatory index (DII), a measure of the inflammatory potential of diet, with risk of hip, lower-arm, and total fracture using longitudinal data from the Women's Health Initiative Observational Study and Clinical Trials. Secondarily, we evaluated changes in bone mineral density (BMD) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
73
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 84 publications
(85 citation statements)
references
References 45 publications
(111 reference statements)
9
73
0
Order By: Relevance
“…The first one was conducted in a large sample of American women, reported finding that high DII scores, indicating a more inflammatory diet, was associated with increased hip fracture risk. However, this finding was limited only to White women [23]. A case-control study in China, confirmed these findings, in both genders, suggesting that pro-inflammatory diet (with lower DII scores) could be positively associated with higher hip fracture risk [24].…”
Section: Introductionmentioning
confidence: 78%
See 2 more Smart Citations
“…The first one was conducted in a large sample of American women, reported finding that high DII scores, indicating a more inflammatory diet, was associated with increased hip fracture risk. However, this finding was limited only to White women [23]. A case-control study in China, confirmed these findings, in both genders, suggesting that pro-inflammatory diet (with lower DII scores) could be positively associated with higher hip fracture risk [24].…”
Section: Introductionmentioning
confidence: 78%
“…In Australia, diet consumed by subjects with asthma was more pro-inflammatory than in healthy controls, and higher DII was associated with impaired lung function [20]. Higher DII scores, especially in males, also were associated with increased risk of colorectal cancer [23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Higher total sodium intake was associated with a 19% significantly lower rate of hip fracture, but this association was attenuated after adjusting for potassium intake . A lower dietary inflammatory index, a measure of the inflammatory potential of diet, was modestly related to a 5% to 8% lower risk of lower arm fracture and any fracture but was unrelated to hip fracture . Higher soft drink consumption (with and without caffeine) has been linked to lower BMD, and in WHI, >14 servings per week was associated with a 26% increased risk of hip fracture (95% CI 1–56%), an association that was independent of many covariates including body mass index .…”
Section: Dietary Intake and Fracture Riskmentioning
confidence: 99%
“…To determine the in ammatory potential of the whole diet, Dietary In ammation Index (DII) has been designed and validated against circulating levels of in ammation [12,13]. This dietary index has linked with several cancers, metabolic diseases, and fractures [14][15][16]. Two longitudinal cohort studies have also shown that higher DII scores were associated with a higher incidence of frailty [17] and decreased appendicular lean mass [6].…”
Section: Introductionmentioning
confidence: 99%